The New Contractual Interpretation in Singapore: From Zurich Insurance to Sembcorp Marine - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2013)
This article seeks in three ways to contribute to the continued refinement of contractual interpretation in Singapore following Zurich Insurance and, more recently, Sembcorp Marine. First, it identifies the key rulings of law derived from the cases. From these, relevant issues in contractual interpretation will be distilled. It is important to identify and distinguish between the exact issues because their conflation will lead to confusion in an area already affected by much complexity due to the concurrent application of statutory and common law principles. Second, this article evaluates the courts' approaches to those issues. The principal difficulty is that there is a need to distinguish between statutory and common law principles. Third, this article suggests some possible reforms in the future. It considers whether it is possible to achieve a commercially sensible approach while keeping within the statutory constraints that bind the courts, or whether legislative reform is required.